Development of disease‐resistant rice by optimized expression of WRKY45. Issue 6 (9th December 2014) - Goto, Shingo; Sasakura‐Shimoda, Fuyuko; Suetsugu, Mai; Selvaraj, Michael Gomez; Hayashi, Nagao; Yamazaki, Muneo; Ishitani, Manabu; Shimono, Masaki; Sugano, Shoji; Matsushita, Akane; Tanabata, Takanari; Takatsuji, Hiroshi
Summary The rice transcription factor WRKY45 plays a central role in the salicylic acid signalling pathway and mediates chemical‐induced resistance to multiple pathogens, including Magnaporthe oryzae and Xanthomonas oryzae pv. oryzae. Previously, we reported that rice transformants overexpressing WRKY45 driven by the maize ubiquitin promoter were strongly resistant to both pathogens; however, their growth and yield were negatively affected because of the trade‐off between the two conflicting traits. Also, some unknown environmental factor(s) exacerbated this problem. Here, we report the development of transgenic rice lines resistant to both pathogens and with agronomic traits almost comparable to those of wild‐type rice. This was achieved by optimizing the promoter driving WRKY45 expression. We isolated 16 constitutive promoters from rice genomic DNA and tested their ability to drive WRKY45 expression. Comparisons among different transformant lines showed that, overall, the strength of WRKY45 expression was positively correlated with disease resistance and negatively correlated with agronomic traits. We conducted field trials to evaluate the growth of transgenic and control lines. The agronomic traits of two lines expressing WRKY45 driven by the OsUbi7 promoter (POsUbi7 lines) were nearly comparable to those of untransformed rice, and both lines were pathogen resistant. Interestingly, excessive WRKY45 expression rendered rice plants sensitive to low temperature and salinity, and stress sensitivity was correlated with the induction of defence genes by these stresses. These negative effects were barely observed in the POsUbi7 lines. Moreover, their patterns of defence gene expression were similar to those in plants primed by chemical defence inducers.